A LABORATORY STUDY ON WETTABILITY ALTERATION OF SANDSTONE USING SILICA NANOPARTICLES - Agung Prasetya, Muhammad
Wettability has a very large influence in determining recovery factor and by altering the wettability will cause more oil to be obtained. Oil will be more easily to be recovered if the reservoir rock is water-wet, which cause the surface tension between the oil and the rock to be low. There are several methods that can be used to altering the wettability of reservoir rock such as the method using thermal and surfactant, but in this research will be focus on the new method. The method is using nanoparticle which are said to be more effective than conventional method. Application of nanotechnology in various field in petroleum industry such as exploration, reservoir, drilling, stimulation, completion, production and processing. In well stimulation, nanotechnology can be used to improve the productivity of wells by changing the interface between surfaces that can be done by wettability alteration so that it can increase oil recovery. The use of nanoparticle is very effective method to be applied in the wettability alteration process. Because the particle size is very small will produce a large surface contact area, so that the effectiveness of their chemical interaction with a surface is greatly increased. The size of nanoparticle is smaller than the pore size of the rock, it caused the nanoparticle can easily penetrate the rock pores and do their job in altering the wettability of rock. Nanoparticle can altering the wettability by coating the rock so that it replaces the contact between rock and oil into rock-nanoparticle-oil so that the most of the rock surface is replaced by nanoparticle and alter the wettability of rock. The research carried out was a laboratory study using silica nanoparticles. Silica nanoparticles are used because they are easy to obtain, relatively low prices and more environmentally friendly than other chemical substances. There are two silica nanoparticles used in this research. Silica nanoparticle A was made by top-down method by grinding and crushing quartz sand using a ball mill for 10 hours to obtain a silica nanoparticle size of 45-184 nm. SEM testing was carried out to determine the size of the silica nanoparticles, while EDS testing was carried out to determine the composition of the silica nanoparticles. Silica nanoparticle B has a size of 12 nm. Nanoparticles are solids that require basic fluids in order to drain nanoparticles through porous media or in other words become nanofluids. Nanoparticles will increase the wetting ability of brine. The nanofluid concentrations used were 0.05 wt%, 0.1 wt% and 0.2 wt%. Wettability alteration can be done through the cantact angle that occurs between the fluid with the formation. Silica nanofluid A with concentrations of 0.05 wt%, 0.1 wt% and 0.2 wt% respectively resulted in contact angles between rock and oil of 13.760, 16.220 and 17.400. Silica nanofluid B with concentrations of 0.05 wt%, 0.1 wt% and 0.2 wt% respectively resulted in contact angles between rock and oil of 16.520, 19.920 and 24.570. The use of silica nanofluid B with a concentration of 0.2 wt% is the optimum concentration because it can change the contact angle from 9.430 to 24.570 , so that it can alter the wettability between oil and rock becomes more non-wetting on the rock surface. The imbibition test is carried out to validate the results of the contact angle test. The imbibition test was carried out for one week with a temperature of 60 0C. Silica nanofluid A with concentrations of 0.05 wt%, 0.1 wt% and 0.2 wt% respectively resulted in oil recovery of 60.05%, 63.68% and 65.65%. Silica nanofluid B with concentrations of 0.05 wt%, 0.1 wt% and 0.2 wt% respectively resulted in oil recovery of 65.15%, 67.75% and 75.63%. The use of silica nanofluid B with a concentration of 0.2 wt% is the optimum concentration because it produces the highest oil recovery of 75.63%. The higher the silica nanofluid concentration, the wetting ability of the brine will increase so that it can altering the wettability between rock and oil become more non-wetting and make the oil recovery getting higher.